OPTIMASI pH DAN WAKTU KONTAK OPTIMUM ADSORBEN Fe3O4-AH TERHADAP ION LOGAM Pb2+ - Riyana, Sindi Dwi; Koesnarpadi, Soerja; Sari, Ika Yekti Liana (PROSIDING SEMINAR NASIONAL KIMIA; Vol 1 No 1 (2022): Prosiding SNK 2022, 2023)
Optimization of pH and optimum contact time of coated magnetite adsorbent (Fe 3 O 4 -AH) against metal ions Pb 2+ has been carried out. Humic acid-coated magnetite adsorbent (Fe 3 O 4 -AH) was prepared using the coprecipitation method with a mass ratio of 1:2 (w/w) and the separation process using an external magnet. Optimization was carried out by batch method using a Pb solution with a concentration of 50 mg/L and an adsorbent mass of 0.1 gram Fe 3 O 4 -AH. The test results show that the optimum pH is at pH 5 with % adsorption of 97.70% and the optimum contact time is at 20 minutes with % adsorption of 99.89%.   Keywords : humic acid, magnetite, adsorption